Import belt set of perm medieval cis-urals in Hungary - Bellavin, Andrei M.; Krylasova, Natalia B.; Podosenova, Ylia A. (Opción, 2019)
In this article, we are studying the material culture of Eastern Europe in the Middle Ages, turned to the so-called Artefacts of Hungarian style, among which a special place is occupied by belt sets’ elements via qualitative comparative analysis as a method. In result, Belt set includes a buckle, buckle tip and three types of pads. Concentration of belt sets finds in burial monuments of the IX-X centuries in Perm Urals indicates that this area may be included in the composition of Hungarian land before they left to the West that remained part of Old Hungarian tribes or their relatives.